Capture of common adverse events (AEs) by patient-reported outcome measures (PROMs) used in clinical trials of immuno-oncology (IO)-based combination therapies in advanced renal cell carcinoma (aRCC). Issue 28 (1st October 2022) - Huo, Stephen; Ejzykowicz, Flavia; Delgado, Andrew; Beauchamp, Karen D.
Abstract : 263 Background: IO-based combination therapies have improved clinical outcomes in aRCC; several are approved for first-line use. AEs can significantly impact quality of life, and IO therapy is associated with AEs that differ from prior standard treatment toxicities. PROMs capture health status directly from patients and often include the symptoms and severity of AEs. Our aim was to assess the extent to which the PROMs used in pivotal trials covered the most common AEs associated with IO combinations. Methods: This was a review of data from four phase 3, randomized, open-label studies of IO-based combinations in previously untreated advanced/metastatic clear-cell RCC (CheckMate 214, CheckMate 9ER, KEYNOTE-426, CLEAR [KEYNOTE-581]). The 10 most common all-grade, all-cause AEs (%) and the PROMs used in each trial were identified. The inclusion of the most common AEs in the PROMs was explored descriptively. Results: The most common AEs and their frequencies varied among the different combination regimens. There was also variation across trials in the PROMs used. Capture of the most common AEs by the PROMs used in each study is summarized in the Table. Conclusions: Current PROMs used in clinical trials of IO combinations for aRCC tend to capture more of the common AEs for IO-IO vs IO-tyrosine kinase inhibitor regimens. PROMs that reflect the unique AE profiles of IO therapies, especially from the patient perspective, may be needed for future trials.Capture of the 10 most common a all-grade, all-cause AEs by PROMs. Study Combination PROMs No. of most common AEs captured b by PROMs AEs not captured by PROMs (frequency) CheckMate 214 Nivolumab + ipilimumab FKSI-19 EQ-5D-3L FACT-G 8 of 10 Rash (39%) Pruritis (33%) CheckMate 9ER Nivolumab + cabozantinib FKSI-19 EQ-5D-3L 5 of 11 Hepatotoxicity (44%) PPE (40%) Stomatitis (37%) Hypertension (36%) Rash (36%) Hypothyroidism (34%) KEYNOTE-426 Pembrolizumab + axitinib FKSI-DRS QLQ-C30 EQ-5D-3L 6 of 13 Hypertension (48%) Hepatotoxicity (39%) Hypothyroidism (35%) PPE (28%) Stomatitis/mucosal inflammation (27%) Rash (25%) Dysphonia (25%) CLEAR (KEYNOTE-581) Pembrolizumab + lenvatinib FKSI-DRS QLQ-C30 EQ-5D-3L 7 of 12 Hypothyroidism (57%) Hypertension (56%) Stomatitis (43%) Rash (37%) Dysphonia (30%) a Some AEs occurred at the same frequency, thus > 10 individual AEs may be counted within the top 10 most frequent. b Fully or partially. EQ-5D-3L, 3-level version of EQ-5D; FACT-G, Functional Assessment of Cancer Therapy-General; FKSI-19, Functional Assessment of Cancer Therapy-Kidney Symptom Index 19; FKSI-DRS, Functional Assessment of Cancer Therapy Kidney Cancer Symptom Index - Disease Related Symptoms; QLQ-C30, European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire 30; PPE, palmar-plantar erythrodysesthesia.